(untitled) (REMUNOM, 2025)
This study proposes an in-depth analysis of anxiety as a psychological condition of high prevalence and global impact, whose relevance has intensified in recent decades, especially in the post-pandemic context. Recent data point to the significant growth of anxiety disorders in different age groups, which justifies the need for research that broadens the understanding of their determinants and forms of management. Based on the guiding question — what are the most relevant biopsychosocial factors for the increase in anxiety disorders and how can integrated approaches contribute to their prevention and treatment? — we seek to develop a critical and interdisciplinary reflection on the topic. The general objective is to analyze anxiety from a biopsychosocial perspective, articulating theoretical and practical aspects. Methodologically, this is a qualitative research, of an exploratory nature, based on a bibliographic review. The sources were selected from scientific databases such as SciELO, PePSIC and Google Scholar, with priority given to publications from the last ten years. The analysis was guided by criteria of scientific relevance, currentness and theoretical validity. Authors such as Beck, Segal, Williams, Teasdale, Hofmann, Padesky and Mooney provide the basis for the discussion, offering support for thinking about coping strategies that integrate different knowledge. This study contributes to the field by emphasizing the importance of integrative and preventive interventions, promoting a more comprehensive, ethical and sensitive approach to the complexity of anxiety in the contemporary world.